KUALITAS AIR MINUM TERNAK AYAM PETELUR DI DESA PILING KECAMATAN PENEBEL KABUPATEN TABANAN DI TINJAU DARI JUMLAH BAKTERI COLIFORM - Suarjana, I Gusti Ketut (Buletin Veteriner Udayana; Vol. 1 No. 2 Agustus 2009, 2012)
A study was carried out to evaluate the water quality in layer farming at Piling Village,Distric and Regency of Tabanan, based on number of Coliform bacteria. The study wasblockrandomized design was asigned in this study. Water samples were collected fromthree sourcess, river, water reservoir and drinking water of pen.Samples were collectedin10 time.The Coliform analysed by most probable number (MPN) Method with nine tubeseries.The result of this study showed that number of Coliform in river, reservoir and place ofdrinking water were 11240 MPN/100 ml, 19800 MPN/100 ml and 35600 MPN/ 100 mlrespectively. Statisticcaly of this study showed amount of Coliform in drinking water offarm layer significant highest (P<0,01) than those reservoir and river. Amount of Coliformin reservoir significant highest (P<0,01) than those river.
Keywords: Coliform; MPN; Layer Farming